Key Drivers of Nglanggeran Tourism Village: The Role of the Privileges Fund - Hatmaka, Herjuna Mai (Universitas Padjadjaran, 2025)
This study examines the effectiveness of the Privileges fund (Danais) in supporting sustainable tourism village development through a systems-based approach, focusing on Nglanggeran Tourism Village, Yogyakarta. The Cross-Impact Matrix Multiplication Applied to Classification (MICMAC) method is used to analyze influence–dependence relationships among 32 variables across four dimensions: social, economic, institutional, and environmental. The findings show that socio-institutional variables particularly community participation, governance capacity, and institutional coordination act as the main driving forces, while economic and environmental dimensions tend to be dependent. These results indicate that the effectiveness of Danais is determined not only by financial allocation, but also by institutional coherence and strong community-based processes. Theoretically, these findings align with second-generation fiscal decentralization theory, emphasizing governance quality and accountability. However, this study has limitations, including reliance on expert judgment from focus group discussions (FGDs), which may introduce subjectivity, and its focus on a single case. In addition, the MICMAC approach has limitations in capturing dynamic interactions and causal relationships. Future research is suggested to integrate quantitative methods, such as econometric or panel data analysis, and to expand comparative studies across regions and countries, particularly in the context of asymmetric decentralization. A longitudinal approach is also needed to better understand the dynamic impacts of fiscal transfers. These efforts are expected to strengthen understanding of optimizing fiscal transfers to support inclusive and sustainable rural development.